Comparison of Riemann and Lebesgue sampling for first order stochastic systems - Astrom, K.J.; Bernhardsson, B.M. (Proceedings of the 41st IEEE Conference on Decision and Control, 2002, 2002)
The normal approach to digital control is to sample periodically in time. Using an analog of integration theory we can call this Riemann sampling. Lebesgue sampling or event based sampling is an alternative to Riemann sampling. It means that signals are sampled only when measurements pass certain limits. In this paper it is shown that Lebesgue sampling gives better performance for some simple systems.